Unforeseen pathologies caused by malaria. (28th December 2017) - Lee, Michelle Sue Jann; Coban, Cevayir
Abstract : The hidden pathologies of malaria Abstract: Individuals from malaria-endemic regions often acquire partial immunity after multiple repeated infections throughout their lives. This partial immunity prevents them from developing severe complications and they often remain asymptomatic with a persistent, low parasite density in the blood, and therefore the necessity for treatment is neglected. These patients with chronic, asymptomatic malaria serve as a reservoir for Plasmodium parasite transmission, becoming a major obstacle for eradication efforts. The constant exposure to malaria infection may have benefits in the short term by conferring protection from acute, severe malaria; however, it may cause substantially more harm in the long term. Rather than the parasite burden itself, the complications induced by the dysregulated immune responses and the tissue damage done by the parasites and their products can cause chronic and irreversible suffering. Furthermore, the complete clearance of parasites in the body may not lead to complete recovery from the disease as complications can still persist. The fact that there are chronic pathologies caused by malaria that mostly remain obscure and have the potential to cause a serious burden has recently been gaining attention. Here, we present and discuss the evidence of unforeseen pathologies and the risks associated with malaria.